A novel classification of supply chain risks: Scale development and validation - Muhammad Saeed Shahbaz; Raja Zuraidah RM Rasi; MD Fauzi Bin Ahmad (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: Supply chain has become an essential element for any organization but risks are the major obstacles in achieving the performance even it can disrupt not only the organization but a whole system. Thus it is compulsory to manage the risks efficiently and effectively. Risk cannot be managed until properly identified, there are numerous studies on risk identification, after comprehensive literature, it has been revealed that the study that identifies overall supply chain risk is scaring. The manufacturing sector of any country is considered as the backbone of any economy, in Malaysia it is the second largest sector in economic contribution and highest in productivity level. The aim of this study is to provide a reliable tool to assess the overall supply chain risks of Malaysian manufacturing through a systematic process. Design/methodology/approach: A detail literature review has been done for categorization of overall supply chain risk sources. Then an instrument has been developed from a pool of items. The questionnaire was purified through pretesting, pilot testing (by the exploratory view) and reliability and validity tests. The data were collected by email from Federation of Malaysian Malaysia (FMM-2017) through systemic probability sampling. Total 132 final responses have been considered for exploratory factor analysis through SPSS 23. Findings: The finding of this study revealed that overall supply chain risks can be categories into seven constructs that are supply side risks, process side risks, demand side risks, logistic side risks, collaboration side risks and environment side risks and the final questionnaire is consisting of 57 items. Research limitations/implications: This study covered tier 1 members of the supply chain. Secondly, the supply chain of manufacturing organizations only has been considered. Practical implications: This study will help the managers to understand what kind of risk sources they can face and which type of risks under these risk sources they should consider while decision making. Originality/value: This article will justify the need for Malaysian manufacturing by providing a validated and reliable instrument for the identification and assessment of their risks under major supply chain risk sources.
Keywords: 650; Supply chain risk management; supply chain risk sources; risk assessment; instrument development; Malaysian manufacturing